2019
DOI: 10.1038/s41379-019-0204-1
|View full text |Cite
|
Sign up to set email alerts
|

Ductal carcinoma in situ of the breast: an update for the pathologist in the era of individualized risk assessment and tailored therapies

Abstract: Ductal carcinoma in situ (DCIS) is a neoplastic proliferation of mammary ductal epithelial cells confined to the ductallobular system, and a non-obligate precursor of invasive disease. While there has been a significant increase in the diagnosis of DCIS in recent years due to uptake of mammography screening, there has been little change in the rate of invasive recurrence, indicating that a large proportion of patients diagnosed with DCIS will never develop invasive disease. The main issue for clinicians is how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 160 publications
(213 reference statements)
0
24
0
2
Order By: Relevance
“…High-grade DCIS often shows comedonecrosis, when the necrotic core extends into the ductal lumen that canundergo calcifications. Necrosis is also constantly and strongly associated with ipsilateral recurrence, with the hazard ratio (HR), in general, above 2.0 [16]. Some studies demonstrated that the risk of ipsilateral recurrence is greater if DCIS with comedonecrosis is only treated with breast conserving surgery, compared to DCIS managed with mastectomy, skin-sparing mastectomy, or breast conserving surgery plus radiotherapy [16].…”
Section: Morphological Features Of Carcinoma In Situmentioning
confidence: 99%
See 3 more Smart Citations
“…High-grade DCIS often shows comedonecrosis, when the necrotic core extends into the ductal lumen that canundergo calcifications. Necrosis is also constantly and strongly associated with ipsilateral recurrence, with the hazard ratio (HR), in general, above 2.0 [16]. Some studies demonstrated that the risk of ipsilateral recurrence is greater if DCIS with comedonecrosis is only treated with breast conserving surgery, compared to DCIS managed with mastectomy, skin-sparing mastectomy, or breast conserving surgery plus radiotherapy [16].…”
Section: Morphological Features Of Carcinoma In Situmentioning
confidence: 99%
“…Zhang et al also disagreeon the role of comedonecrosis, suggesting that there is no correlation between necrosis and the risk of invasive local recurrence [15]. demonstrated that the risk of ipsilateral recurrence is greater if DCIS with comedonecrosis is only treated with breast conserving surgery, compared to DCIS managed with mastectomy, skin -sparing mastectomy, or breast conserving surgery plus radiotherapy [16]. Zhang et al also disagreeon the role of comedonecrosis, suggesting that there is no correlation between n ecrosis and the risk of invasive local recurrence [15].…”
Section: Morphological Features Of Carcinoma In Situmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiologically, DCIS represents 20-25% of all new BC cases diagnosed [31] and this incidence is increasing as a result of an upgraded resolution of breast mammography [32]. Around 80% of the DCIS are identified by the presence of micro-calcifications and the remaining 20% by the detection of architectural deformation in mammography screening [33,34] (Figure 1B2).…”
Section: Relevance Of MD In the Dcis-to-icd Transitionmentioning
confidence: 99%